2017
DOI: 10.3892/mmr.2017.6691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory actions of various functional food materials including glucosamine on synovial cells

Abstract: The anti-inflammatory actions of glucosamine (GlcN) on arthritic disorders involve the suppression of inflammatory mediator production from synovial cells. GlcN has also been reported to inhibit the activation of the p38 mitogen-activated protein kinase (MAPK) pathway. The present study aimed to determine the cooperative and anti‑inflammatory actions of functional food materials and evaluated the production of interleukin (IL)‑8 and phosphorylation of p38 MAPK in IL-1β-activated synovial cells, incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Synovial cell cultures exposed to lipopolysaccharide treatment, instead, were reported in the literature as a model to study the protective and anti-inflammatory effects of HA alone or in combination with CS and GlcN [34, 35]. In addition, through the NF-κB activation and IL-8 production, the synovial cells have been used to evaluate the anti-inflammatory response of food supplements with other potentially bioactive molecules (e.g., HA, collagen peptides, Boswellia serrata , devil’s claw, or curcumin).…”
Section: Discussionmentioning
confidence: 99%
“…Synovial cell cultures exposed to lipopolysaccharide treatment, instead, were reported in the literature as a model to study the protective and anti-inflammatory effects of HA alone or in combination with CS and GlcN [34, 35]. In addition, through the NF-κB activation and IL-8 production, the synovial cells have been used to evaluate the anti-inflammatory response of food supplements with other potentially bioactive molecules (e.g., HA, collagen peptides, Boswellia serrata , devil’s claw, or curcumin).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK, a major signaling in inflammatory cells, can be induced by inflammatory cytokines and lead to the expression of various MMP, adhesion molecules, and proinflammatory genes ( Yamagishi et al ., 2017 ). Studies have shown that the JNK pathway, as well as p38, is required for the MMP production of inflammatory mediator-stimulated or activated synovial fibroblasts ( Nishitani et al ., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our multimodal approach included spinal manipulation, electrical stimulation, and soft-tissue mobilization to help preserve biomechanics, ROM, and neuromuscular integrity [25][26][27] ; calcium, vitamin D, magnesium, and low-level laser therapy to help support bone growth [27][28][29] ; and glucosamine, chondroitin, and methlylsulfonylmethane to help support bone growth, preserve cartilage, reduce pain and inflammation, and increase ROM. [30][31][32][33][34] We considered the use of proteolytic enzymes to help reduce inflammation, but patient allergy prevented their use. The patient achieved normal ROM and return to activity milestones 1 month earlier than expected for this injury, 35 did not require pain medication outside of the immediate postoperative recovery room, missed only 2 days of work (surgery days), and had no complications at 3 years postoperation.…”
Section: Discussionmentioning
confidence: 99%